Soviet-German Non-Aggression Pact (1939) and “Red Menace” in USA Press Assessments - S. O. Buranok; Y. A. Levin (Научный диалог)
The question of the evolution of the USA press attitude to the foreign policy of the USSR is considered. The article presents the results of the analysis of American newspapers in the aspect of the formation of the image of the “red menace.” The study of this information phenomenon will allow to understand more precisely how the representations formed through the press influenced the Soviet-American relations. The main arguments by which the authors justify the key role of the 1939 Pact in creating a new image of the USSR are given. The novelty of the study is seen in the fact that the estimates of the 1939 Pact, given by American journalists, are analyzed. The influence of British newspapers on American assessments of the Pact is discussed. It is noted that the study of the USA press will provide an opportunity to more deeply illuminate American ideas about practical approaches to the development of international relations in the context of the transformation of the world order before the Second World War. The analysis of the press showed that during 1939 in the American public discourse there was a change of priority approaches: the image of the USSR evolved from the “red menace” to a potential ally. It is shown that this problem is relevant in practical terms - for the analysis of modern information processes in American society.